2009
DOI: 10.1083/jcb.200904105
|View full text |Cite
|
Sign up to set email alerts
|

Real-time in vivo imaging of p16Ink4a reveals cross talk with p53

Abstract: Expression of the p16Ink4a tumor suppressor gene, a sensor of oncogenic stress, is up-regulated by a variety of potentially oncogenic stimuli in cultured primary cells. However, because p16Ink4a expression is also induced by tissue culture stress, physiological mechanisms regulating p16Ink4a expression remain unclear. To eliminate any potential problems arising from tissue culture–imposed stress, we used bioluminescence imaging for noninvasive and real-time analysis of p16Ink4a expression under various physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
157
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 67 publications
4
157
0
Order By: Relevance
“…Our data also showed that shikonin increased expression of p16, further contributing to inhibition of phosphorylation of Rb in both K1 and FTC133 cells, and NAC dramatically abolished this effect. These observations suggest that shikonin inhibits cell growth by modulating the activity of the p16/Rb/E2 factor (E2F) pathway, as supported by previous studies showing that ROS-induced upregulation of p16 is one of the mechanisms regulating senescence, which keeps the balance between regeneration and cancer (34,35). Given that metastasis is the major cause of cancer-related death, we investigated the effect of shikonin on cell migration and invasion in this study.…”
Section: Discussionmentioning
confidence: 71%
“…Our data also showed that shikonin increased expression of p16, further contributing to inhibition of phosphorylation of Rb in both K1 and FTC133 cells, and NAC dramatically abolished this effect. These observations suggest that shikonin inhibits cell growth by modulating the activity of the p16/Rb/E2 factor (E2F) pathway, as supported by previous studies showing that ROS-induced upregulation of p16 is one of the mechanisms regulating senescence, which keeps the balance between regeneration and cancer (34,35). Given that metastasis is the major cause of cancer-related death, we investigated the effect of shikonin on cell migration and invasion in this study.…”
Section: Discussionmentioning
confidence: 71%
“…Despite these advantages, p16 INK4A also has apparent limitations as an in vivo biomarker of senescence. First, there are forms of in vitro senescence that are not characterized by p16 INK4A expression 18,[78][79][80] . At least under some circumstances, the absence of p16 INK4A expression might be compensated by upregulation of p15 INK4B (REFS [81][82][83] or by the expression of CDKN2C (also known as INK4C) 84 .…”
Section: Markers Of Senescencementioning
confidence: 98%
“…Another possibility implicates increased expression of DNMTs induced by the oncogene. 9 Although unlikely, oncogenes might also be able to increase DNMT enzymatic activity thus disrupting the balance that keeps specific gene loci active (Fig. 1).…”
Section: Philadelphia Chromosomementioning
confidence: 99%